Simplified Lawsuits in Dispute Resolution Within Sharia Economic Law in Indonesia - Solihin, Dadin; Setiadi, Setiadi; Bunyamin, Bubun; Yusup, Deni Kamaludin; Ridwan, Ahmad Hasan (Universitas Islam Sultan Agung, 2022)
This research is based on the numerous disputes in Sharia economic law within Sharia Business Financial Institutions, legal aid in the field of Sharia economic law, and civil matters that have not been well resolved. The Regulation of the Supreme Court of the Republic of Indonesia (PERMA RI) No. 4 of 2019 regulates the resolution of Sharia economic law disputes in a simplified manner. However, the socialization of this regulation to the public is still lacking, causing frequent obstacles in the implementation of this PERMA RI. This research is a literature study with a juridical approach aimed at analyzing the implementation of PERMA RI in the resolution of Sharia economic cases. The primary data in this research includes PERMA RI No. 4 of 2019, PERMA RI No. 14 of 2016, PERMA RI No. 2 of 2015, and PERMA RI No. 1 of 2016. Several relevant cases are used as important data to analyze the implementation of these regulations. The results of this research show that the process of simplified lawsuits in the resolution of Sharia economic disputes, which is expected to be easier, faster, and cheaper in court, has not been realized in accordance with PERMA RI. This needs to be a concern for the Supreme Court because most Sharia economic dispute cases involve companies and the public. If the Supreme Court regulations are not properly implemented in court proceedings, it will create a space for injustice. Therefore, the socialization of these Supreme Court regulations needs to be enhanced by academics and practitioners so that their implementation in the future can be better.